Pattern of acquisition of rotavirus antibody in children followed up from birth to the age of three years - Alexandre C. Linhares; Valéria R. Melo; Joana D'Arc P. Mascarenhas; Yvone B. Gabbay; Ronaldo B. de Freitas (Sociedade Brasileira de Medicina Tropical (SBMT), 1989)
Nine hundred and forty-eight serum samples from 83 children living in Belem, Brazil, collected'within their first three years of life, were testedfor the presence of group- specific rotavirus-antibody by an enzyme-linked immunosorbent assay (ELISA) blocking-test. Passively transferred maternal antibody lasted about two and half months; subsequentely, low levels of rotavirus antibody started to appear at seven months, reaching a peak at eleven months of age. From one year onwards positivity gradually increased, reaching highest values at 34 months of life. Individual responses were examined in sera from 61 children who were followed up since birth to three years of age: 38 (62,3%) ofthem developed a long-term immunity following first infection; eleven (18.0%) children developed a short-term immunity after first infection by rotavirus; seven (11.5%) had no antibody response within their first three years of life; and 5 (8.2%) showed positive antibody response from birth to three years old. Amostras de soro, em número de 948, foram coletadas de 83 crianças, ao longo de seus três primeiros anos de vida, e testadas quanto àpresença de anticorpos grupo-especificos para rotavirus por um teste de bloqueio, utilizando-se o ensaio imunoenzimático (ELISA). Observou-se que anticorpos transferidos passivamente pela mãe persistiram por cerca de dois e meio meses; subseqüentemente, baixos níveis de anticorpos para rotavirus começaram a aparecer aos sete meses de idade, atingindo um pico por volta dos onze. A partir de um ano apositividade aumentou gradualmente, alcançando os mais altos valores aos 34 meses de vida. Respostas imunes individuais foram avaliadas em 61 crianças acompanhadas desde o seu nascimento até os três anos de idade, obtendo-se os seguintes resultados: 38 (62,3%) delas desenvolveram imunidade de longa duração, após a primo-infecção; 11 (18,0%) indivíduos apresentaram anticorpos específicos que se mantiveram por um intervalo de tempo relativamente curto; 07 (11,5%) não exibiram qualquer resposta imune ao ...